Introduction to the Heritage Building Medan City Using Augmented Reality - Ikhwan, Ali; Buyung Nasution, Adnan (Politeknik Ganesha Medan, 2022)
The city of Medan is the largest city in North Sumatra and has a variety of ethnicities and diverse cultures, one of which is the Malay ethnic deli. The cultural identity of the Deli Malays in Medan is inseparable from the relics of the Malay Deli Sultanate, one of which is the heritage of the building. The lack of information on the relics of the building and the ignorance of the public about this information so that people are less familiar with the relics of the Malay Deli Sultanate building. Therefore, we need a mobile application that can help the public to find out information about the relics of the Malay sultanate and the shape of the building in 3D so that people can see 360 ​​degrees of the architectural animation of the heritage which is equipped with the history of the building's legacy. Augmented Reality (AR) is a method between the virtual world in the form of images (2D) with 3D animation then projected in real time and so on. This application uses the Markerless Augmented Reality (User Defined Target) method, which is making the marker formation by selecting the target selected by the user using a cellphone camera. The stages in this application include design design, 3D object modeling to application development. Based on the research above, it can be concluded that the application made can provide information about the relics of the Malay Deli Sultanate building. It is hoped that in the future objects from the Malay deli sultanate building will be added as well as displaying the interior and exterior supporting the heritage buildings such as fences, gardens, and others.